2017
DOI: 10.3389/fmicb.2017.01711
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Shifts in the Intestinal Microbiota of Salmonella Infected Chickens in Response to Enrofloxacin

Abstract: Fluoroquinolones (FQs) are important antibiotics used for treatment of Salmonella infection in poultry in many countries. However, oral administration of fluoroquinolones may affect the composition and abundance of a number of bacterial taxa in the chicken intestine. Using 16S rRNA gene sequencing, the microbial shifts in the gut of Salmonella infected chickens in response to enrofloxacin treatments at different dosages (0, 0.1, 4, and 100 mg/kg b.w.) were quantitatively evaluated. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 61 publications
6
37
3
1
Order By: Relevance
“…Here, we investigated the effects of enrofloxacin on the colonization of S. Typhimurium in the intestinal tracts of chickens. Our results showed that on days 7 and 14, S. Typhimurium was highly abundant in the cecum contents of mice treated with antibiotics, similar to previous reports (9,15,17). Thus, our findings showed that different concentrations of enrofloxacin altered the ability of S. Typhimurium to colonize the gut in chickens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we investigated the effects of enrofloxacin on the colonization of S. Typhimurium in the intestinal tracts of chickens. Our results showed that on days 7 and 14, S. Typhimurium was highly abundant in the cecum contents of mice treated with antibiotics, similar to previous reports (9,15,17). Thus, our findings showed that different concentrations of enrofloxacin altered the ability of S. Typhimurium to colonize the gut in chickens.…”
Section: Discussionsupporting
confidence: 91%
“…Quinolones, such as enrofloxacin, affect the composition and number of bacterial species in the chicken gut (9), thereby altering resistance to pathogen invasion. Indeed, bacteria residing in the gut can mediate the colonization of S. Typhimurium in the body by producing short-chain fatty acids (SCFAs), such as propionic acid, which inhibits S. Typhimurium growth by influencing the intracellular pH (10).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no counterparts of the susceptible or resistant E. coli isolates were detected before drug administration. Sequencing of the 16S rRNA of the intestinal microbiota of specific-pathogen-free (SPF) chickens also confirmed that the number of E. coli isolates at the initial phase was low (10). All 330 E. coli isolates with low to high levels of resistance to FQs were selected from the middle-dosage group (4 mg/kg of b.w.)…”
Section: Discussionmentioning
confidence: 75%
“…Coprobacillus, Clostridium, and Eubacterium have an important role in the production of SCFAs essential amino acids and the digestion of non-starch polysaccharides, which stimulate the production of SCFAs for metabolic balance [68,70]. Likewise, it has been reported that the reduction of Clostridium and the maintenance of Eubacterium and Coprobacillus levels could be related to the effectiveness of the treatments since they represent a positive effect in the maintenance of intestinal homeostasis [70][71][72].…”
Section: Discussionmentioning
confidence: 99%